Invariant curves for planar competitive and cooperative maps. Issue 6 (3rd June 2018) - Kulenović, M. R. S.; Merino, O.
Abstract: In this paper we present results on the existence of invariant curves for planar maps that are monotone with respect to either the south-east or north-east ordering. Some of these curves are the stable or unstable manifolds of hyperbolic fixed points (saddle points) or non-hyperbolic fixed points, and are also the boundary of basins of attraction of such points.